Manufacturing of Fibrous Composites for Engineering Applications - Xu, Jinyang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Fibrous composites are one type of high-performance composite material featuring the presence of fiber-like reinforcement impregnated with different matrix bases, which have taken a prominent position in diverse engineering applications because of their unique mechanical/physical properties and outstanding structural functions. Manufacturing is a critical procedure to ensure the target dimensions and desired quality of fibrous composites. This involves technical issues frequently encountered in the fabrication, processing, and machining of these composite materials. To date, great endeavors have been made in the past few decades to address manufacturing issues associated with the engineering applications of fibrous composites. Precision manufacturing of these advanced composites has thus become a hot research topic in both academia and industry. Recent advances have been achieved covering both experimental and numerical investigations of manufacturing science and technology of fibrous composites. This Special Issue sought to report the latest research findings achieved by scholars worldwide focusing on the manufacturing science of fibrous composites for engineering applications. Well-organized papers covering both experimental and numerical studies of fabricating, processing, and machining fibrous composites were all welcomed. It was our hope that this Special Issue will provide a platform for academic and industrial researchers to share and disseminate their original research results on all manufacturing aspects of fibrous composites.